HUBUNGAN FLEKSIBILITAS DENGAN KESEIMBANGAN DINAMIS PADA LANJUT USIA - Kiasati Nur Amajida (2021)
The increase in life expectancy indicates that there is progress in the health sector, and it requires the improvement in life quality. Improving life quality in the elderly to raise independency out of the others is important, especially on flexibility as it is an important factor in the development of human movement. The decrease in flexibility will result in decrease in muscle strength, and will further result in balance disorders that affect daily life. This research seeks to determine the correlation between flexibility and dynamic balance in the elderly. To investigate the correlation, the researcher implemented a descriptive correlative research with a cross-sectional design. The research population consisted of the elderly at Kalitunsawa Indonesia Foundation, Bekasi with a total sample of 48 people. The parameters used were the 'chair sit and reach' test to measure flexibility and the 'time up go' test to measure dynamic balance. The analysis results using SPSS 21 obtained several Spearman's rho Sig. (2-tailed); the 'chair sit and reach' test and the 'time up go' obtained a value of p = 0,011x. Based on the research results, it can be concluded that there is significant correlation between flexibility and dynamic balance in the elderly.